2012
DOI: 10.1007/s00246-012-0488-0
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Arterial Thrombosis After Cardiac Catheterization In Infancy: Impact of Doppler Ultrasound for Diagnosis

Abstract: Femoral arterial thrombosis (FAT) is a nonnegligible complication after cardiac catheterization (CC) in infancy. The aim of this study was to evaluate the impact of Doppler ultrasound (US) for diagnostic work-up after catheterization. We compared standard follow-up (FU) without Doppler US by relying on clinical signs of FAT with advanced FU using Doppler US of the femoral vessels. Between January and December 2009, we evaluated the rate of FAT in infants <12 months of age using a multicenter, prospective obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…In line with previously reported data, our study clearly shows that arterial thrombosis after CC predominantly affects neonates and infants aged <12 months 4–6 9 11 21 25 26 31. An overall analysis of patients with a large range of age may therefore underestimate the incidence of thrombosis 4 8 10 12 15 18 20 21 23 26 33…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In line with previously reported data, our study clearly shows that arterial thrombosis after CC predominantly affects neonates and infants aged <12 months 4–6 9 11 21 25 26 31. An overall analysis of patients with a large range of age may therefore underestimate the incidence of thrombosis 4 8 10 12 15 18 20 21 23 26 33…”
Section: Discussionsupporting
confidence: 90%
“…The fact that only 57 of the 171 patients had undergone routine Doppler ultrasound suggests major bias in the recruitment of patients. Although ultrasound was not performed routinely in our patients, using clearly defined clinical diagnostic criteria, the incidence of arterial thrombosis in our study was similar to the incidence reported by Kocis et al and significantly increased compared with the ones reported by Hanslik et al 12 and Knirsch et al 13. As long as no validation data are available on the use of Doppler ultrasound as compared with angiography, which is still considered the gold standard for the diagnosis of arterial thrombosis, our data indicate that a well-defined and intensive clinical monitoring of children after CC can be considered a valuable diagnostic tool.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations